Glial cells in the mammalian olfactory bulb - Zhao, Dan; Hu, Meigeng; Liu, Shaolin (Frontiers in Cellular Neuroscience, 2024)
The mammalian olfactory bulb (OB), an essential part of the olfactory system, plays a critical role in odor detection and neural processing. Historically, research has predominantly focused on the neuronal components of the OB, often overlooking the vital contributions of glial cells. Recent advancements, however, underscore the significant roles that glial cells play within this intricate neural structure. This review discus the diverse functions and dynamics of glial cells in the mammalian OB, mainly focused on astrocytes, microglia, oligodendrocytes, olfactory ensheathing cells, and radial glia cells. Each type of glial contributes uniquely to the OB's functionality, influencing everything from synaptic modulation and neuronal survival to immune defense and axonal guidance. The review features their roles in maintaining neural health, their involvement in neurodegenerative diseases, and their potential in therapeutic applications for neuroregeneration. By providing a comprehensive overview of glial cell types, their mechanisms, and interactions within the OB, this article aims to enhance our understanding of the olfactory system's complexity and the pivotal roles glial cells play in both health and disease.Astrocytes originate from neural progenitor cells and engage in a meticulously structured journey toward the OB during neural development (Zhan et al., 2017). This migration is facilitated through the protrusion of astrocytic extensions that cling to radial glial strands. These strands serve as a structural framework imperative for cellular motility (Ling et al., 1989).